From gross to net wages in German administrative data sets - Henrike Junge (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
[Introduction] This data documentation describes selected ways of how to analyze net wages in the weakly anonymous Sample of Integrated Labour Market Biographies 1975-2010 (SIAB) or other administrative data sets provided by the Institute for Employment Research (IAB). Among other things, these data sets provide information about dependently employed persons in Germany and their gross wages over time. Due to the large number of included observations, the data sets are often used in empirical studies of the German labor market. However, net wages are not reported in the data sets and important income tax-relevant characteristics which would allow for a simulation of individual tax burdens are not included. Therefore, labor market studies based on IAB data that want to take effects of (income) taxation into account must impute the tax burdens as a first step of their analyses. This data documentation discusses different ways to perform this imputation and compares their ability to produce reliable predictions.
Keywords: 330